Longitudinal Associations Between Serum Cytokine Levels and Dementia - Kim, Ju-Wan; Stewart, Robert; Kang, Hee-Ju; Bae, Kyung-Yeol; Kim, Sung-Wan; Shin, Il-Seon; Yoon, Jin-Sang; Kim, Jae-Min (Frontiers in Psychiatry, 2018)
Background: The purpose of this study was to investigate whether long-term inflammation is related to the incidence of dementia in a prospective observational study. Methods: In total, 732 Korean community-dwelling elderly people > 65 years were evaluated at baseline. Of the 625 without dementia, 518 (83%) were followed over a 2.4-year period, and the incidence of dementia was determined. Cytokine [interleukin (IL)-1α, IL-1β, IL-6, IL-8, and tumor necrosis factor (TNF)-α] levels were measured at baseline and follow-up. The individual and combined effects of cytokine levels on dementia were evaluated after adjusting for potential covariates (lifestyle factors, demographics, disability, cognitive function, and presence of the APOE e4 allele) and a Bonferroni correction. Results: Incident dementia was associated with increased serum cytokine levels after 2 years; the association remained significant for TNF-α, IL1-α, and IL-1β concentrations even after applying a Bonferroni correction. The analysis of the combined effects of the five cytokines showed independent associations between increases in the summed number of higher cytokine levels, between baseline and follow-up. However, incident dementia was not expected based on higher baseline pro-inflammatory cytokine levels. Conclusion: Our results suggest that dementia may precede changes in serum cytokine levels and inflammatory processes, rather than resulting from elevated pro-inflammatory cytokines.